APPLICATION OF THE CONTENTS OF CORPORATE GOVERNANCE IN THE PRACTICE OF RISK MANAGEMENT IN ISLAMIC BANKS - Dr-Haider Mohammed Ali Baniata (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The paper dealt with the application of the contents of corporate governance in the practice of risk management in Islamic banks according to the rules of corporate governance (protection of shareholders’ rights, the responsibilities of the board of directors, disclosure and transparency, the role of stakeholders, the environment of control and control). The study used descriptive and analytical methods to answer its questions. The study community consisted of all three employees of Islamic banks in Jordan. A random sample of (100) employees of the three banks was selected, which is 2973(1)employees in 2017. The study found that there is a positive impact when applying the contents of corporate governance in the practice of risk management in Islamic banks. Recommended the adoption of corporate governance standards and rules based on scientific and jurisprudential consolidation and standardization of rules and regulations governing banking relations between banks and stakeholders.